Virtual Clothing Modeling and Fabric Simulation: a Systematic Review (ModaPalavra e-periódico, 2025)
This article aims to analyze the main advances in fashion modeling within the physical and semantic worlds through a Systematic Literature Review (SLR). The SLR was conducted using the Parsifal tool, following the guidelines of Claes (2012). After selecting the articles, the PRISMA (2020) method was employed to organize the data, while the Mendeley© platform was used for reading and managing references. As part of the analysis, two main concepts were established: the Semantic World, related to the virtual environment, and the Physical World, linked to the real and tangible world. The analyzed articles were categorized into these two fields, highlighting intersections and practical applications. The results revealed that, in general, studies tend to prioritize the Semantic World, using the Physical World mainly as a support to achieve the proposed project objectives.
Keywords: systematic review; virtual; 3D modeling; clothing modeling